Padrões transformacionais da relação predicado-argumento dos substantivos predicativos em português brasileiro - Martinez, Ryan Marçal Saldanha Magaña (2019)
This work aims at describing the relations between predicative nouns and their arguments, establishing their frequency while seeking syntactic and semantic correlations with such numbers. In order to describe predicate and argument sequences observed in a Brazilian Portuguese newspaper corpus, we employ the transformational theory used in Lexicon-Grammar. This theory apprehends different syntactic manifestations as transformations departing from a kernel sentence, i.e., in Portuguese, a sentence containing a single predicate and its arguments in SVO order. Noun predicates kernel sentences include auxiliary verbs "have", "give" or "do" immediately prior to the predicative element; those are named support verbs. Also, we attribute semantic roles to the identified arguments. The methodology used to identify noun predicates had as its main element the possibility of reducing a certain sequence to kernel sentences through introspective and empirical means. Hence, we define the transformations of noun predicates occurring along the corpus, analyzing predicate, arguments and support verb sequences, which we call "strings". Subsequently, we established the frequency of strings and correlated them to kernel sentences and the semantic roles identified. The results show that: 1- predicative nouns exhibit some general manifestation patterns, emerging more commonly as noun groups; 2- some of their transformations tend to lead into other transformations; 3- the kernel sentence form, including the elementary support verb, determines or bears relevance to some transformations; 4- the distribution of semantic roles presents an isomorphism with kernel sentences, but bear little correlation with transformations.